2015
DOI: 10.4102/ojvr.v82i1.850
|View full text |Cite
|
Sign up to set email alerts
|

Virulence gene profiles of avian pathogenic <i>Escherichia coli</i> isolated from chickens with colibacillosis in Bulawayo, Zimbabwe

Abstract: Colibacillosis, a disease caused by avian pathogenic Escherichia coli (APEC), is one of the main causes of economic losses in the poultry industry worldwide. This study was carried out in order to determine the APEC-associated virulence genes contained by E. coli isolates causing colibacillosis in chickens. A total of 45 E. coli isolates were obtained from the diagnostics and research branch of the Central Veterinary Laboratories, Bulawayo, Zimbabwe. These isolates were obtained from chickens with confirmed ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 34 publications
(71 reference statements)
5
24
2
Order By: Relevance
“…This result is higher than the result that said by (Mbanga and Nyararai, 2015) who said that percent of PCR for amplification of fimH gene of E. coli was (33.3%) of APEC isolates and lower than the result obtained by (Roussan et al, 2014) who identified fimH gene with a percentage (94%) by using PCR.…”
Section: Suspectedcontrasting
confidence: 64%
“…This result is higher than the result that said by (Mbanga and Nyararai, 2015) who said that percent of PCR for amplification of fimH gene of E. coli was (33.3%) of APEC isolates and lower than the result obtained by (Roussan et al, 2014) who identified fimH gene with a percentage (94%) by using PCR.…”
Section: Suspectedcontrasting
confidence: 64%
“…So in this study, the detection of the species-specific gene is considered the main step to complete the investigation of virulence genes. The iss, fimH, and iutA genes were selected due to their common prevalence in APEC isolated from broiler samples via PCR [19,[31][32][33]. Our findings revealed that the most prevalent virulence gene was iss (93.3%), followed by iutA (46.6%), and fimH gene (20%); this highest incidence of iss and iutA genes among the pathogenic cases was in accordance with that in the study by Rodriguez-Siek et al [34] (81.5% and 80.2%, respectively) and Rocha et al [35] (73.8% and 45.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Mbanga et al (2015) detected all of the 12 VGs (iutA, hlyF, ompT, frz, sitD, fimH, kpsM, sitA, sopB, uvrY, pstB and vat) they screened for in APEC in South Africa. The three most prevalent VGs detected in the 45 APEC were iutA (80%), fimH (33%) and hlyF (24%) with genes kpsM, pstB and ompT being detected in only 2.2% of the isolates.…”
Section: The Prevalence Of Apec Related Vgsmentioning
confidence: 98%
“…However, direct comparisons between research studies is difficult due to: the high genetic diversity of APEC; the variety of VGs associated with and used to classify APEC; large variability in sampling strategies and microbiological methods Johnson et al, 2008b;Mbanga and Nyararai, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation